Three new oxazoline alkaloids from Gymnotheca chinensis. Issue 8 (2nd August 2016) - Xiao, Shi-Ji; Guo, Da-Le; Zhang, Mao-Sheng; Chen, Fang; Ding, Li-Sheng; Zhou, Yan
Abstract: Three novel oxazoline alkaloids, 1-oxa-3-azaspiro [4.5] dec-2-ene-8-one (1 ), 1-oxa-3-azaspiro [4.5] dec-2, 6-diene-8-one (2 ), and 1-oxa-3-azaspiro [4.5] dec-10-methoxy-2, 6-diene-8-one (3 ) were isolated from the methanol extract of the whole plant of Gymnotheca chinensis . The chemical structures were established by means of spectroscopic analysis including one- and two-dimensional NMR spectroscopy.